AN OVERVIEW OF NANOELECTRONICS AND NANODEVICES - OYUBU AKPOVI OYUBU; OKPEKI UFUOMA KAZEEM (Journal of Engineering Studies and Research)
Nanoelectronics is a nascent area of making electronic devices at the atomic scale to utilize small-scale 'quantum' characteristics of nature. As the name suggests, Nanoelectronics refers to employing nanotechnology in building electronic devices/components; especially transistors. Thus, transistor devices which are so small such that inter-atomic cooperation and quantum mechanical characteristics cannot be ignored are known as Nanoelectronics. This article presents Nanoelectronics and Nanodevices, which are the critical enablers that will not only enable mankind to exploit the ultimate technological capabilities of electronic, mechanical, magnetic, and biological systems but also have the potential to play a part in transforming of the systems thus giving rise to new trends that will revolutionize our life style.